Educational Attainment And Intergenerational Mobility In India: Evidence From Nss 75th Round Survey Data - Bharti, Anil Kumar; Nag, Susanta; Kumar, Rajesh; Gupta, Preeti; Gagandeep (Migration Letters, 2024)
The study of intergenerational mobility has been a longstanding area of interest among social scientists. The concept of intergenerational mobility assesses the extent to which individuals can improve their social or economic standing compared to that of their parents. Since education is an important determinant of an individual’s lifetime earnings and general well-being, so educational mobility significantly influences social or economic mobility between generations. The present study stands out from previous research by examining the relationship between one’s education and occupation, health, wealth accumulation, and economic independence in old age. Additionally, it investigates how these educational outcomes contribute to the heterogeneity in children’s educational attainment. For analysing the objective, NSS 75th round data has been used. The study found a significant positive association between the educational attainment of individuals and their occupation, consumption quintile, economic independence at old age and self-reported health status. Further, the study also found a positive association between the educational level of parents and that of their children suggesting that the children of highly educated parents are more likely to be better educated compared to the children of less educated parents, who are likely to stuck at lower levels of education. This has been validated by the ordinal logistic regression results. Further, the models exhibit differences in terms of significance and effect sizes, highlighting the importance of considering specific variable combinations in understanding educational outcomes. The odds ratios significantly increase after controlling for economic factors. The strong positive relationship between children’s education and parental education persisted when controlling for economic factors such as household consumption expenditure and occupation classes.